Dynamic Capital Structure under Managerial Entrenchment - Zwiebel, Jeffrey (American Economic Review, 1996)
This paper develops a model in which managers voluntarily choose debt to credibly constrain their own future empire-building. Dynamically consistent capital structure is derived as the optimal response in each period of partially entrenched managers trading-off empire-building ambitions with the need to ensure sufficient efficiency to prevent control challenges. A policy of capital structure coordinated with dividends follows naturally, as do implications for the level, frequency, and maturity structure of debt as a function of outside investment opportunities. Additionally, the model yields new testable implications for security design, and changes in debt and empire-building over managerial careers.